for Reorientasi Capaian Pembelajaran Matematika Fase E Menuju Kompetensi Keberlanjutan (Education for Sustainable Development) - Intan Wahyuna; Nurcholif Diah Sri Lestari; Rahmadina Dwi Orissa; Devid Rezqi Firmansyah (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze and reorient the Mathematics Learning Outcomes (Capaian Pembelajaran/CP) of Phase E to align with eight key competencies of Education for Sustainable Development (ESD). Using a modified Krippendorff’s content analysis model with three stages, unitizing, coding, and reorienting, supported by a survey of high school students' perceptions in East Java, the study found that current Mathematics CPs remain largely conceptual-procedural and lack explicit sustainability integration. Nevertheless, each domain shows reorientation potential: Number through contexts of energy efficiency and sustainable resource use; Algebra and Functions through mathematical modeling of sustainability issues such as population growth and carbon emissions; Geometry through environmentally responsive spatial design; and Data and Probability through data literacy and ethical reasoning using environmental data. Survey findings indicate students’ strong cognitive and affective readiness for contextual and sustainability-oriented mathematics learning. Overall, the study highlights the need to shift mathematics education from learning about sustainability toward learning as and for sustainability, positioning mathematics as a tool for systemic, reflective, and ethical reasoning in addressing real-world sustainability challenges.